Holmium laser versus thulium laser enucleation of the prostate: a matched-pair analysis from two centers - Pirola, Giacomo Maria (Ther Adv Urol, 2018)
BACKGROUND: The aim of our study was to compare perioperative and functional outcomes of two different prostatic laser enucleation techniques performed in two high-volume centers: 100 W holmium laser enucleation of the prostate (HoLEP) (Lyon, France) and 110 W thulium laser enucleation of the prostate (ThuLEP) (Varese, Italy). MATERIALS AND METHODS: A nonrandomized, observational, retrospective and matched-pair analysis was performed on two homogeneous groups of 117 patients that underwent prostate laser enucleation in the HoLEP or ThuLEP centers between January 2015 and April 2017, following the classical ‘three lobes’ enucleation technique. The American Society of Anesthesiologists (ASA) score and prostate volume were the main parameters considered for matching the patients between the two groups. Patients on anticoagulant therapy, with documented detrusor hypoactivity or hyperactivity or with the finding of concurrent prostate cancer were excluded from the study. Follow up was assessed at 3, 6 and 12 months after surgery. RESULTS: Median enucleation and morcellation time was 75.5 and 11.5 min, respectively, in the HoLEP group versus 70.5 and 12 min, respectively, in the ThuLEP group (p = 0.001 and 0.49, respectively). Enucleated adenoma weight was comparable (44 g versus 45.6 g, p = 0.60). Energy index (3884.63 versus 4137.35 J/g, p = 0.30) and enucleation index (0.57 versus 0.6 g/min, p = 0.81) were similar in the two groups. Catheterization time was comparable (1 versus 1 day; p = 0.14). The International Prostate Symptom Score and Quality of Life score significantly decreased, as well as maximal urinary flow rate. Median prostate-specific antigen (PSA) drop 1 year after surgery was 2.1 ng/ml in the HoLEP group (−52.83%) versus 1.75 ng/ml in the ThuLEP group (−47.85%) (p = 0.013). CONCLUSION: Both HoLEP (100 W) and ThuLEP (110 W) relieve lower urinary tract symptoms in a comparable way with high efficacy and safety, with negligible clinical differences.